The Effect of The-Teaching-With-Analogies Model Application on Learning Science to Creative Thinking Skill of Student on Junior High School - Justica, Aulia Astari; Azrai, Eka Putri; Suryanda, Ade (Biosfer: Jurnal Pendidikan Biologi, 2015)
The learning process in schools hasn’t been able to cultivate the habit of thinking in high levels, one of which is creative thinking. This skill can be improved by the-teaching-with-analogies model. The research aimed to know the effect of the teaching-with-analogies model application to students creative thinking. This research was done at Labschool Jakarta Junior High School on May 2014. Samples in the research were VII A, VII B, VII E and VII F with purposive sampling. Samples were decided by simple random sampling, which had 30 students from each class. The methods used quasi experiment with posttest-only control design. Based on calculation, the average score of student in experiment class was 80 and the average score of student in control class was 72. Normality test was tested by Kolmogorov-Smirnov test and homogenity test was tested by F-test. Based on calculation, the data from experiment were normally distributed and homogeny. This research showed that implementation of the-teaching-withanalogies model has affected to creative thinking skills of student on junior high school.